PENGARUH MODEL KOOPERATIF TIPE STAD BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR MATERI HAK DAN KEWAJIBAN MURID KELAS III SDN DANAU INA OESAPA - Sine, Astrid; Koroh, Taty R.; Nawa, Netty E. A. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted due to the low learning outcomes of third-grade students in Pancasila Education, particularly on the topic of rights and obligations at SDN Danau Ina Oesapa. This condition was reflected in students’ low achievement scores and limited participation during the learning process. The learning activities were still dominated by conventional teaching methods, with limited use of innovative learning models and media, which affected students’ understanding of the material. Therefore, this study aimed to determine the effect of the STAD-type cooperative learning model assisted by animated video media on students’ learning outcomes in the rights and obligations material. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 36 students divided into an experimental class and a control class. Data were collected through pretests, posttests, observation, and documentation. The data analysis techniques included validity and reliability tests, normality and homogeneity tests, and hypothesis testing using the Independent Sample t-Test with SPSS version 27. The results showed that students who were taught using the STAD-type cooperative learning model assisted by animated video media achieved better learning outcomes than those who were taught using conventional methods. The experimental class obtained a mean posttest score of 78.6, while the control class achieved a mean score of 65.8. Hypothesis testing revealed a significance value (2-tailed) of < 0.001, which was lower than 0.05. Therefore, the STAD-type cooperative learning model assisted by animated video media had a significant positive effect on students’ learning outcomes in Pancasila Education, particularly on the rights and obligations material.